The Application of The Jigsaw Method to Improve Students’ English Learning Outcomes at SMAN 7 Gowa - Amaniar Rahmah; Maemuna Muhayyang; Ahmad Talib (State University of Makassar, 2026)
This research aimed to determine the effectiveness of the Jigsaw method in improving students’ English learning outcomes at SMAN 7 Gowa. The research employed a quantitative approach using a pre-experimental design with one group pre-test and post-test. The population of this research consisted of all tenth-grade students of SMAN 7 Gowa totaling 114 students, while the sample was 30 students of class X IPA A selected through cluster random sampling. The instrument used in this research was a multiple-choice test administered as a pre-test and a post-test. The data were analyzed using descriptive and inferential statistics. The result of the research showed that the students’ mean score in the post-test was higher than the mean score in the pre-test. The result of hypothesis testing showed that the significance value was 0.000, which was lower than the significance level of 0.05. Therefore, it can be concluded that the Jigsaw method was effective in improving students’ English learning outcomes.Key words: jigsaw method, students’ english learning outcomes.